GOOD CORPORATE GOVERNMENT, KINERJA KEUANGAN TERHADAP PENGUNGKAPAN SUSTAIBABILITY REPORT - Novi Yanti (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
Disclosure of the Sustaibability Report which is one of the obligations that must be carried out by the company to attract investors who see the performance of a company not only from financial but also non-financial aspects. In this study, testing the effect of Good Corporate Government (Board of Directors, Board of Commissioners, Audit Committee) and Financial Performance (Profitability, Company Size, and Capital Structure) on the disclosure of Sustaibability Reports in manufacturing companies for the 2018-2021 period. This research is a quantitative research using secondary data with non-probability sampling technique, for analysis using multiple linear regression analysis. The test results from independent to dependent variables are 3 influential variables, namely the board of directors, profitability and capital structure, while the independent board of commissioners, audit committee and company size have no effect